Potential of live pathogen vaccines for defeating the COVID‐19 pandemic: History and mechanism - Chen, Ji‐Wang; Chen, Ji‐Ming (Journal of medical virology, 2020)
The whole world has entered a terrible crisis with a huge and increasing number of human deaths and economic losses in fighting the pandemic of COVID‐19 caused by the novel coronavirus termed SARS‐CoV‐2. The live pathogen vaccine (LPV) strategy, which originated in ancient China for fighting smallpox, has been applied successfully by US military recruits for decades to control acute respiratory diseases caused by types 4 and 7 adenoviruses. This strategy has also been widely employed in veterinary medicine. These facts suggest a fast way out of the current pandemic crisis, namely that SARS‐CoV‐2 could be directly used as a live vaccine. Beyond the two traditional mechanisms to guarantee the LPV's safety (the LPV seed strain is properly selected; the LPV is inoculated bypassing the respiratory sites of pathology), three novel mechanisms to further ensure the LPV's safety are available (the virus replication is inhibited with early use of an antiviral drug; symptomatic LPV recipients are cured with convalescent plasma; the LPV is inoculated in the hot season). This LPV strategy has multiple potential advantages over other options and could reduce morbidity and mortality greatly as well as the economic loss caused by the pandemic. The safety and efficacy of this strategy should be investigated strictly using animal experiments and clinical trials, and even if the experiments and trials all support the strategy, it should be implemented with enough caution. Highlights ●The world has entered a terrible crisis in fighting the COVID‐19 pandemic. ●Live pathogen vaccines (LPV) have defeated infectious diseases caused by adenoviruses. ●The LPV strategy has been widely employed in veterinary medicine. ●The LPV strategy could be a way out of the COVID‐19 pandemic crisis. ●Five mechanisms can be employed to ensure the safety of the LPV of SARS‐CoV‐2. ●The LPV strategy should be examined with animal experiments and clinical trials.